If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z = 5(x + h) Reorder the terms: z = 5(h + x) z = (h * 5 + x * 5) z = (5h + 5x) Solving z = 5h + 5x Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Simplifying z = 5h + 5x
| 3c=7.35 | | a^2-12ax+32x^2=0 | | c^2-cy-12y^2=0 | | 2b-22/b-11 | | (xy^2+x)dx+(xy^2+y)dy=0 | | 1. 3a=4a+8 | | 3x+21=108 | | -(-5v+y)+6(2y-5v)= | | 3*-5y=15 | | 12x+18y=1 | | y=-x^2+4x+45 | | 3*0-5y=15 | | 2x-1/2x=0 | | 10=2(y-3)-6y | | 2.5x-7.5=x | | x-2*-2=6 | | -40+6p+p^2= | | 2xyz-10xy-49y= | | 3(x-2)+12=6x+5-3x | | 3x^2-22x-7=0 | | -75727.82/87.08= | | 39.76-(6.46)+(53.78)= | | 41.4-8.8(-75.2)(-114.5)+2.3= | | -1530-(-573)= | | 10+5x=5y | | 4-(-0.25)-0.5= | | c^2-17c+72= | | 0=3x^4-10x^3+3x^2+12x-4 | | 9-8-2(7-5)= | | 17x-.57=1.43x-.077x-3.524 | | .17x-.57=1.43x-.0077x-3.524 | | ((5n^2)-14n)(n^2)=0 |